Farming Sustainability in Peatlands Following Restoration Programme in West Kalimantan - Jajat Sudrajat; Evi Gusmayanti; Rossie Wiedya Nusantara; Siti Sawerah (Jurnal Ilmu Pertanian Indonesia, 2026)
The Indonesian government's peat restoration program, which began in 2016, is alleged to have an impact on the sustainability of peatland farming, because rewetting has the potential to cause waterlogging, limiting the crop commodities that can be cultivated. This project will look at the viability of small-scale farming on restored peatlands. To fulfill the study's objectives, we used a combination of quantitative and qualitative methods. The quantitative technique included an analysis of agricultural income to determine the economic sustainability, whereas the qualitative approach explains social sustainability. The environmental sustainability was assessed using the carbon rescue acquired after rewetting. The findings revealed that rewetting had little effect on the income from vegetable and fruit crops. The farming income, which remains relatively high, demonstrates that farming's economic sustainability is viable. Similarly, the social dimension does not detract from the sustainability aspect, because the rewetting of the land did not significantly alter the social structures and institutions that had been built in the farmer's community. Meanwhile, from an environmental standpoint, the impact of rewetting is quite favorable, as every 1 cm increase in water table level has the potential to conserve at least 0.71 tons of CO2 per acre per year, or around IDR 13,888−26,993. Keywords: carbon rescue, farming, peatland restoration, rewetting